Mechanisms involved in reproductive damage caused by gossypol in rats and protective effects of vitamin E - Santana, Andréia T. [UNESP]; Guelfi, Marieli [UNESP]; Medeiros, Hyllana C. D. [UNESP]; Tavares, Marco A. [UNESP]; Bizerra, Paulo F. V. [UNESP]; Mingatto, Fábio E. [UNESP] (Santana et al., 2015)
Gossypol is a chemical present in the seeds of cotton plants (Gossypium sp.) that reduces fertility in farm animals. Vitamin E is an antioxidant and may help to protect cells and tissues against the deleterious effects of free radicals. The aim of this study was to evaluate the mechanisms of reproductive toxicity of gossypol in rats and the protective effects of vitamin E. Forty Wistar rats were used, divided into four experimental groups (n = 10): DMSO/saline + corn oil; DMSO/saline + vitamin E; gossypol + corn oil; and gossypol + vitamin E. Fertility was significantly reduced in male rats treated with gossypol in that a significant decrease in epididymal sperm count was observed (P < 0.05) and the number of offspring was significantly reduced in females mated with them (P < 0.05). This dysfunction was prevented by vitamin E. Gossypol caused a significant increase in the activity of the enzymes glutathione peroxidase (P < 0.01) and glutathione reductase (P < 0.01), but vitamin E did not reduce the enzyme activities (P > 0.05). The levels of reduced glutathione and pyridine nucleotides in testis homogenate were significantly reduced by gossypol (P < 0.05 and P < 0.01, respectively) and this reduction was accompanied by increased levels of oxidized glutathione (P < 0.05). Vitamin E showed a preventive effect on the changes in the levels of these substances. Gossypol significantly increased the levels of malondialdehyde (P < 0.01), a lipid peroxidation indicator, whereas treatment with vitamin E inhibited the action of the gossypol. Vitamin E prevented a decrease in mitochondrial ATP induced by gossypol (P < 0.05). This study suggests that the reproductive dysfunction caused by gossypol may be related to oxidative stress and mitochondrial bioenergetic damage and that treatment with vitamin E can prevent the infertility caused by the toxin.
Keywords: Gossypol; Fertility; Oxidative stress; Bioenergetics; Antioxidant system; Vitamin E